KAJIAN META- ANALISIS INOVASI PENGAJARAN USUL FIQH DI INDONESIA - Faisal Husen Ismail; Arwansyah Bin Kirin; Cha Adenan Muhammad; Abd Shakor Borham; Muhammad Masruri (Hudan Lin Naas: Jurnal Ilmu Sosial dan Humaniora, 2021)
Abstract: Studies related jurisprudence growing rapidly around the Muslim world, including Indonesia. Hence there is need to analyze previous studies on inovation teaching jurisprudence that has been undertaken to identified pattern and disposition of the research conducted. The objective of this study was to determine the pattern and research gaps exist in the field that have been done earlier researchers. Qualitative methods were used in this study. The study systematically analysed articles related innovation in teaching jurisprudence in Indonesia from 2009 to 2018. The findings from the analysis show most of the studies that have been conducted focusing on the need to reform of jurisprudence in Indonesia. Therefore, analysis showed that the approach using qualitative methods most often used where the field study is the most preferred method. The findings of this study can be used as a reference to the study of jurisprudence related to teaching innovation in Indonesia. This article provides suggestions for further research related to innovation in teaching jurisprudence.Keyword: Innovation, teaching jurisprudence, knowledge of jurisprudence, Indonesia, Meta-Analysis.